Effects of different brewing processes on the volatile flavor profiles of Chinese vinegar determined by HS-SPME-AEDA with GC-MS and GC-O. (November 2020) - Al-Dalali, Sam; Zheng, Fuping; Sun, Baoguo; Zhou, Chenxi; Li, Ming; Chen, Feng
Abstract: Effects of different brewing processes, such as the solarization process (i.e. with or without), selection of different types of rice as a raw material (i.e. normal or sticky rice), and addition of flavoring materials (i.e. presence or absence of spices or sugar), on the aroma profiles of three types of Chinese vinegars were investigated. These three vinegars were the Longmen aromatic sweet rice vinegar (LASRV), Longmen aromatic rice vinegar (LARV), and Longmen rice vinegar (LRV). Headspace solid-phase microextraction combined with gas chromatography-mass spectrometry (HS-SPME-GC-MS) and HS-SPME-aroma extract dilution analysis combined with gas chromatography-olfactometry (HS-SPME-AEDA-GC-O) were used to identify and quantify the volatile compounds, as well as the aroma-active compounds in the Longmen vinegars. Among the total of 68 volatile compounds that were identified, 49 were confirmed by their corresponding chemical standards. The results showed that the LASRV sample contained higher concentrations of acids, alcohols, esters, sulfides, acetal, and aromatic hydrocarbons because of effects of the solarization process and the presence of added sugar. The LARV sample was found to contain more aldehydes, pyrazines, ketones, phenols, lactone, and oxazoles, which might be contributed by the solarization process, as well as the addition of spices. Highlights: The solarization process showed more contributions to the aroma profiles of Longmen vinegars. 2-Ethyl-4, 5-dimethyloxazole and ethyl 3-(methylthio)propionate were identified for the first time as aroma-active. Different brewing processes distinguished clearly the aroma profiles of vinegars. Spices added to the vinegar contributed to its final odor intensities.